2007
DOI: 10.1038/sj.sc.3102087
|View full text |Cite|
|
Sign up to set email alerts
|

Spasticity may defend skeletal muscle size and composition after incomplete spinal cord injury

Abstract: Design: Cross-sectional. Objectives: (1) To determine the effects of the level of spinal cord injury (SCI) on skeletal muscle, intramuscular fat (IMF) cross-sectional areas (CSAs) and relative IMF; (2) to determine the relation, if any, of spasticity to each of these variables after incomplete SCI. Settings: In-patient study at the Shepherd Center, Atlanta, GA, USA. Methods: Thirteen individuals with incomplete SCI were classified according to their level of injury into a high level of injury group (HLI, C5-C7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 41 publications
(81 reference statements)
4
74
0
Order By: Relevance
“…11 We were unable to accept our hypothesis because our current findings showed that a long-term administration of the same dose of oral baclofen does not interfere with the protective effects of spasticity on body composition and metabolic profile that were noted earlier. [7][8][9] Moreover, a potential protective effect was observed on glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 We were unable to accept our hypothesis because our current findings showed that a long-term administration of the same dose of oral baclofen does not interfere with the protective effects of spasticity on body composition and metabolic profile that were noted earlier. [7][8][9] Moreover, a potential protective effect was observed on glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients have difficulty comprehending that the goal of treatment is spasticity control and not elimination, because a threshold level of spasticity is necessary to maintain muscle mass and enhance glucose homeostasis. 7,8 For example, those with MAS 42 have a greater skeletal muscle cross-sectional area by 420%. 7 Moreover, extensor spasticity has recently been shown to be correlated with a reduction in FM and increase in FFM after motor complete SCI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations